2020
DOI: 10.1126/sciadv.aay8544
|View full text |Cite
|
Sign up to set email alerts
|

Activation of adenosine A 2A receptor by lipids from docosahexaenoic acid revealed by NMR

Abstract: The lipid composition of the plasma membrane is a key parameter in controlling signal transduction through G protein–coupled receptors (GPCRs). Adenosine A2A receptor (A2AAR) is located in the lipid bilayers of cells, containing acyl chains derived from docosahexaenoic acid (DHA). For the NMR studies, we prepared A2AAR in lipid bilayers of nanodiscs, containing DHA chains and other acyl chains. The DHA chains in nanodiscs enhanced the activation of G proteins by A2AAR. Our NMR studies revealed that the DHA cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…A recent NMR study of A 2A AR embedded in lipid nanodiscs showed that DHA chains increased G protein activation [ 166 ]. A 2A AR bound to the full agonist was found in an equilibrium involving multiple active conformations of TM7.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent NMR study of A 2A AR embedded in lipid nanodiscs showed that DHA chains increased G protein activation [ 166 ]. A 2A AR bound to the full agonist was found in an equilibrium involving multiple active conformations of TM7.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
“…Smaller discs also increase the risk of spurious interactions between the extramembranous regions of the embedded protein and the scaffold protein [ 273 ]. Commonly used variants in solution-state NMR studies of GPCRs are MSP1D1 and MSP1D1E3, which give disc sizes of ~9.6 and ~12 nm, respectively, requiring deuteration of the receptor for sufficient spectral quality [ 166 , 196 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
See 1 more Smart Citation
“…On the picosecond-to-nanosecond timescale, some A 2A AR amino acids increase side-chain dynamics, while others become stabilized 18 . Sub-millisecond conformational variability was shown for both apo-form 19 and agonist-bound A 2A AR 16,17,20 .…”
Section: Introductionmentioning
confidence: 97%
“…The current information about A 2A AR conformational dynamics is based mostly on several reported NMR experiments [16][17][18][19][20][21][22] . In response to ligand binding, different A 2A AR amino acids either alter their sole stable conformations or vary relative probabilities of coexisting stable conformations 16,17 .…”
Section: Introductionmentioning
confidence: 99%